Let's simplify the expression step by step:
-
Combine the like terms: \[ 2\sqrt{8} + 2\sqrt{8} + \sqrt{28} = 4\sqrt{8} + \sqrt{28} \]
-
Now, let's simplify \(\sqrt{8}\) and \(\sqrt{28}\):
- \(\sqrt{8} = \sqrt{4 \cdot 2} = 2\sqrt{2}\)
- \(\sqrt{28} = \sqrt{4 \cdot 7} = 2\sqrt{7}\)
-
Substitute those back into the expression: \[ 4\sqrt{8} + \sqrt{28} = 4(2\sqrt{2}) + 2\sqrt{7} = 8\sqrt{2} + 2\sqrt{7} \]
So the answer is: \[ 8\sqrt{2} + 2\sqrt{7} \]
None of the provided options directly match this final result. However, if we were to simplify \(4\sqrt{8} + \sqrt{28}\), we could keep it in that form. It looks like \(4\sqrt{8} + \sqrt{28}\) would be the response that reflects the calculations.